Teachers’ Perceptions of Project-Based Learning in Strengthening Mathematical Literacy and Problem-Solving Skills - Priyanti, Nita (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Preschool education represents an essential foundation for the development of children’s mathematical literacy and problem-solving skills, which are critical for daily life and future learning. This study aims to analyze teachers’ perceptions of the use of Project-Based Learning in strengthening mathematical literacy and problem-solving skills among preschool children. A quantitative approach was employed by collecting data through a questionnaire distributed to early childhood educators via Google Forms. The collected data were analyzed using SPSS and presented in the form of tables and graphical visualizations to provide a systematic and measurable overview of teachers’ responses. The findings indicate that, based on teachers’ perceptions, Project-Based Learning is perceived to enhance children’s engagement, understanding of mathematical concepts, and enthusiasm for learning, which in turn supports the development of their problem-solving skills. These results suggest that Project-Based Learning is viewed by teachers as a relevant and effective pedagogical approach for early childhood education, provided that it is supported by appropriate teacher guidance, well-designed projects, and learning environments that are aligned with children’s developmental levels.